2022
DOI: 10.1093/sleep/zsac140
|View full text |Cite
|
Sign up to set email alerts
|

Does sleep duration moderate genetic and environmental contributions to cognitive performance?

Abstract: While prior research has demonstrated a relationship between sleep and cognitive performance, how sleep relates to underlying genetic and environmental etiologies contributing to cognitive functioning, regardless of the level of cognitive function, is unclear. The present study assessed whether the importance of genetic and environmental contributions to cognition vary depending on an individual’s aging-related sleep characteristics. The large sample consisted of twins from six studies within the Interplay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…Sleep duration (short sleep) is the trait most significantly enriched by the Blue module genes. In a large-scale twin study, Vo et al [27] recently reported a large genetic influence on semantic fluency and episodic memory at shorter sleep durations. Interestingly, the SNPs and their mapped genes of the Blue module provide a molecular genetic architecture to the estimated genetic contribution from the twin study.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration (short sleep) is the trait most significantly enriched by the Blue module genes. In a large-scale twin study, Vo et al [27] recently reported a large genetic influence on semantic fluency and episodic memory at shorter sleep durations. Interestingly, the SNPs and their mapped genes of the Blue module provide a molecular genetic architecture to the estimated genetic contribution from the twin study.…”
Section: Discussionmentioning
confidence: 99%